Plasma enhanced-nutmeg essential oil solid liposome treatment on the gelling and storage properties of pork meat batters. (February 2020) - Zhu, Yulin; Li, Changzhu; Cui, Haiying; Lin, Lin
Abstract: Nutmeg ( Myristica fragrans Houtt ) essential oil (NEO) encapsulated solid liposomes (NEO-SLP) and cold nitrogen plasma treated NEO-SLP (P-NEO-SLP) were added into pork tenderloins meat batters and their effect on the oxidation of proteins and lipid, thermal gelatin and water holding capacity were studied. The addition of NEO-SLP and P-NEO-SLP impacted the microbial contamination, lipid oxidation, oxidation and decomposition of proteins in pork meat batters. Furthermore, these two particles modified the viscoelasticity and interfered with the aggregated process of meat proteins, as revealed by the rheological test. Also, SEM results showed NEO-SLP and P-NEO-SLP addition increased and strengthened the network formed by protein-protein interaction as more proteins that less oxidized were involved in protein entanglement, thus resulting in more water entrapped in the protein gels induced by the capillary force of protein network, as revealed by NMR study. Finally, the texture and color of pork meat batters were greatly preserved by P-NEO-SLP treatment, as compared with other samples. Highlights: Plasma treated NEO-SLP (P-NEO-SLP) showed high preservative effect. P-NEO-SLP increased the water holding capacity of pork meat batters. Gels had fine networks after P-CEO-SLP treatment. P-NEO-SLP strengthened the gel integrity and storage stability of meat batters.